Pengaruh Audit Kinerja Sektor Publik dan Pengawasan Fungsional terhadap Akuntabilitas Publik pada Komisi Yudisial - Fadhila Zakva Anjani; Rachmat Fadly (Journal on Education, 2023)
The Government System has undergone changes which are used to support management and responsibility for Public Sector Performance Audits, Functional Supervision and Public Accountability to provide the public with access to information regarding government policies, regulations and actions. The purpose of this research is to analyze and explain the influence of public sector performance audits on public accountability, analyze and explain the effects of functional oversight on public accountability and analyze and influence the effects of performance audits and functional oversight on public accountability. The research method uses explanatory research. This type of research was because researchers wanted to explain the relationship between performance auditing and functional oversight of public, accountability. In contrast, the approach taken in this study is quantitative. The results of this study indicate that the T-test analysis of Performance Audit has a Significant Influence on Publik Accountability in the Judicial Commission obtains results (0.004<0.05), Functional Oversight has a Significant Influence on Publik Accountability obtains results (0.000<0.05), and test analysis F Performance Audit and Functional Oversight Have a positive effect on Publik Accountability at the Judicial Commission obtaining results (0.000 <0.05). So that improvements to the Publik Audit system and Functional Oversight as part of internal management will increase Publik Accountability to the Central/Regional government. In this case, the Judicial Commission is vital in ensuring the strength of audit mechanisms and internal oversight to create better accountability by implementing clear, precise policies, procedures, and mandates and effective, efficient reporting and handling mechanisms.